Real exchange rates in small open OECD and transition economies: comparing apples with oranges? - Balázs Égert; Kirsten Lommatzsch; Amina Lahrèche-Révil (Center for Economic Studies and ifo Institute (CESifo), 2007)
We find that productivity gains in tradables cause an appreciation of the real exchange rate via both tradable and nontradable prices in the CEE-5 and have no affect in the Baltic countries, while they lead to a depreciation of the real exchange rate of tradables in OECD economies that overcompensates the appreciation due to nontradable prices. Rising net foreign liabilities lead to a real appreciation in the Baltic countries instead of the expected depreciation found in OECD and CEE-5 countries. These differences are due to the different impact of the fundamentals on the real exchange rate depending on the time horizon studied.
Keywords: C15; E31; F31; O11; P17; 330; real exchange rate; equilibrium exchange rate; productivity; tradables; Balassa- Samuelson effect; Kaufkraftparität; Kleines-offenes-Land; Übergangswirtschaft; Osteuropa; OECD-Staaten